P2X7 Receptor Blockade Protects Against Acrolein-Induced Bladder Damage: A Potential New Therapeutic Approach for the Treatment of Bladder Inflammatory Diseases - Taidi, Zhinoos; Zhou, Tommy; Moore, Kate H.; Mansfield, Kylie J.; Liu, Lu (Frontiers in Pharmacology, 2021)
Inflammatory conditions of urinary bladder have been shown to be associated with urothelial damage and loss of function. The purinergic P2X7 receptor has been implicated in several inflammatory conditions. The aim of this study was to investigate the role of P2X7 receptor in acrolein-induced inflammatory damage using porcine urinary bladder. For this purpose, an ex-vivo model of porcine urothelial damage induced by direct instillation of acrolein into the whole bladder lumen was used. To determine the role of P2X7 receptor, bladders were pre-incubated with a selective P2X7 receptor antagonist, A804598 for 1 h. The effects of acrolein-induced urothelial damage on bladder function were assessed by examining bladder wall contractile response, structure changes, apoptosis and oxidative stress in bladder tissues. Acrolein treatment led to significant damage to urothelium histology, tight junction expression and contractile responses. Acrolein also induced apoptosis in the mucosa layer. All these acrolein induced responses were attenuated by pre-treatment with the P2X7 receptor antagonist A804598. Acrolein also significantly induced DNA oxidation in submucosal layer, however, P2X7 receptor antagonism did not show any protective effect towards acrolein-induced oxidative stress. These findings suggested that P2X7 receptor is involved in acrolein-induced damages to the urothelium, therefore P2X7 receptor antagonists may be a new therapeutic option for the treatment of bladder inflammation.